2015
DOI: 10.2196/mhealth.3713
|View full text |Cite
|
Sign up to set email alerts
|

Finding a Depression App: A Review and Content Analysis of the Depression App Marketplace

Abstract: BackgroundDepression is highly prevalent and causes considerable suffering and disease burden despite the existence of wide-ranging treatment options. Mobile phone apps offer the potential to help close this treatment gap by confronting key barriers to accessing support for depression.ObjectivesOur goal was to identify and characterize the different types of mobile phone depression apps available in the marketplace.MethodsA search for depression apps was conducted on the app stores of the five major mobile pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
232
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(247 citation statements)
references
References 83 publications
(94 reference statements)
11
232
0
4
Order By: Relevance
“…As such evaluations that decry that lack of evidence-based principles within apps [21] or arguments against apps because of the overwhelming lack of rigorous research evaluation [22] is unlikely to impact consumer behavior. Consumers were much more likely to be interested in a variety of sources of information about expected benefit including user reviews, anecdotes from friends or family members, or doctor recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…As such evaluations that decry that lack of evidence-based principles within apps [21] or arguments against apps because of the overwhelming lack of rigorous research evaluation [22] is unlikely to impact consumer behavior. Consumers were much more likely to be interested in a variety of sources of information about expected benefit including user reviews, anecdotes from friends or family members, or doctor recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…10 We found, however, that only 70% of apps produced by our search were relevant to mental health, echoing prior results of low relevancy. 7 Most apps resulting from our search were for symptom relief, containing approaches to improving mental health that may benefit only milder symptoms. Although low-intensity mindfulness and acceptance-based interventions, 11 as well as relaxation and audio interventions, 12 and self-monitoring 13 may alleviate some symptoms of depression and anxiety, effects likely depend on symptom severity and without clinician support, app users may be unaware of when to seek professional help.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, few empirical studies have examined the information made available to potential users choosing mental health-related apps. 7 To address this gap, in this article, we use content analysis to help answer: (a) whether apps found appeared relevant to the mental health key term searched for and/or mental health in general, (b) what types of approaches to improving mental health were provided within apps, and (c) whether descriptions included information, which may be important to someone with a mental health concern, such as information about privacy safeguards and evidence of app effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This degree of concordance is higher than observed in reviews of other physical and mental health apps, and possibly reflects a higher degree of involvement from professional institutions in app development. For example, Nicholas et al found that only 4% of apps for bipolar disorder were developed by institutions [12], and similarly Shen et al reported that universities and institutions accounted for only 4.2% of developers of depression-related apps [13]. In contrast, institutions accounted for approximately half of developers of the reviewed suicide prevention apps.…”
Section: Summary Of Evidencementioning
confidence: 99%